Commercial Mediation: Commercial Conflict Panacea or an Affront to Due Process and the Justice Ideal? - Feehily, Ronán (Comparative and International Law Journal of Southern Africa, 2022)
The article analyses the potential negative impact of the commercial mediation process, gleaned from experience in foreign jurisdictions, to assess the lessons that can be learned in order that such negative effects can be avoided as the process develops as a viable alternative to judicial adjudication and arbitration in South Africa. The limits of mediation and the need for court adjudication, both for those cases that require it and for providing the shadow of the law within which commercial mediation functions are assessed. The impact of the process on court backlogs, reducing trial rates, the potential costs to lawyers, clients and justice and the potential baleful impact of power imbalances in commercial mediation are analysed and discussed. The article proceeds to assess the approach of the South African legislature to defining mediation in various statutes and reveals that much of the criticism of the process is based on the fact that many varied processes are collectively described as mediation. The article concludes with a focus on the need to appropriately describe the process, as the issues discussed do not invalidate the rationale for encouraging the use of commercial mediation; they play an instrumental role in defining its appropriate limits.